Use of Oral Empagliflozin to Obtain Optimal Blood Sugar Levels for Conducting 18F-FDG PET-CT in Patients with Hyperglycemia—A Pilot Study - Mahato, Abhishek; Jain, Anurag; Prakash, V.S; Nair, Rajesh; Joshi, Richa; Paliwal, Dharmesh; Tiwari, Awadhesh; Khandpur, Sukhanshi; Singh, Harkirat (World Journal of Nuclear Medicine, 2023)
Background Flourine-18 fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG PET-CT) is a well-established imaging modality for the evaluation of patients with oncological and nononcological conditions. The underlying principle of imaging is the preferentially increased glucose consumption by cancer cells, due to overexpression of glucose type 1 receptors that are insulin independent. Thus, one of the factors that leads to decreased sensitivity of an 18F-FDG PET-CT is elevated blood sugar levels, leading to decreased glucose uptake by cancer cells due to competitive inhibition.A significant percentage of patients scheduled for PET-CT scan has diabetes mellitus type II as a comorbid condition and often has elevated random blood sugar (RBS) precluding an upfront PET-CT evaluation. Such cases must be rescheduled. This causes delay in the evaluation and management of such patients.Empagliflozin is a novel sodium glucose type 2 inhibitor that prevents tubular reabsorption of glucose and increases renal glycosuria resulting in decreased blood sugar. This drug does not cause significant hypoglycemia or increase endogenous insulin secretion. This study was undertaken to evaluate a potential role for empagliflozin in facilitating optimal blood sugar control in patients with hyperglycemia on the day of the scheduled PET scan.Methods This is an interventional prospective study and patients detected to have RBS more than 200 mg/dL on the day of the scheduled scan were included in the study. The patients were administered two tablets of 10 mg empagliflozin and kept under observation. Samples for RBS were taken at approximately 2nd and 4th hour post administration by bedside method. These patients underwent scan on the same day after adequate sugar control and when an RBS of less than 200 mg/dL was achieved. The primary outcome studied was change in RBS values in the patient cohort and evaluation of PET SUV (standardized uptake value) compared with the rest of the patients scheduled on the same day. Secondary outcome was assessment of any side effects in the patients.Results Total of 10 patients were found to have elevated blood sugar (RBS > 200 mg/dL; irrespective of being on medication) and did not meet the evaluation criteria for a PET-CT scan on the scheduled day. Following administration of the drug, all 10 patients were able to attain blood sugar levels and fulfill the criteria for undergoing a PET-CT scan. No obvious side effect was noted in any of the patient. The SUV values of the patient cohort were comparable with the rest of the patient scanned on the day.Conclusion In this pilot study, 20 mg of empagliflozin (2 tablets of 10 mg) appears to be a safe and effective method for achieving optimal decrease in the RBS without causing hypoglycemia or hyperinsulinemia. It can be safely employed in the subset of population with RBS between 201 and 300 mg/dL to adequately bring the sugar levels at acceptable levels RBS less than 200 mg/dl and fulfill the FDG PET-CT criteria as per European Association of Nuclear Medicine (EANM) norms.
Keywords: 18F-FDG; empagliflozin; optimal blood sugar; PET-CT; SGLT2